Is a widening gender wage gap necessarily caused by a glass ceiling? a case study from Uganda. (1st April 2012) - ,
Abstract : Contrary to what is generally assumed, the gender wage gap and the glass ceiling may not necessarily be positively related. An exploratory analysis of aggregate public service personnel data for Uganda shows that the gender wage gap is small at the middle level of management, whereas it is twice as high at the top. At the same time, the share of women in top positions appears to be twice as high as at the middle ranks. Hence, it seems that in the context of a very patriarchal culture, women 'have to pay' for being promoted to the top rather than that there is a linearly thickening glass ceiling that would drive a widening gender wage gap. The exploratory data analysis suggests that the glass ceiling effect may have an equally vicious partner in the shape of a glass ceiling trade-off.